Analysis of the Canvas Business Model in the Sustainability of the Lampit MSME Business in the Wetland Area of North Hulu Sungai Regency - Setio Utomo; M. Hasanur Arifin; Rangga Novansyah; Ria Anis Rosyidah; Adella Nagma Agnesia; Dimas Azhar Maulana (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The aim of this research is to analyze Customer Segment, Customer Relationship, Channel, Revenue Structure, Value Proposition, Key Activities, Key Resources, Cost Structure and Key Partners which influence the Sustainability of Lampit MSME Businesses in the Wetland Area of Hulu Sungai Utara Regency. The research method using the research approach used is a quantitative approach which can be interpreted as a research method based on the philosophy of positivism, used to research certain populations or samples with sampling techniques which can generally be classified, data collection using research instruments, data analysis is quantitative/ statistics with the aim of testing predetermined hypotheses. The collected data is then analyzed using the PLS (Partial Least Square) analysis model using the SmartPLS package computer program. The results of data processing using the PLS (Partial Least Square) analysis model using the SmartPLS package computer program, the results were that Customer Segment was proven to have a significant influence on Business Sustainability, Customer Relationship was proven to have a significant influence on Business Sustainability, Channel was proven to have a significant influence on Business Sustainability, Revenue Structure is proven to have a significant influence on Business Sustainability, Value Proposition is proven to have a significant influence on Business Sustainability, Key Activities are proven to have a significant influence on Business Sustainability, Key Resources are proven to have a significant influence on Business Sustainability, Cost Structure is proven to have a significant influence on Business Sustainability, and Key Partners are proven to be influential significant impact on the Sustainability of the Lampit MSME Business in the Wetland Area of Hulu Sungai Utara Regency Keywords: Business Model Canvas, Business Sustainability